Visionary Leadership Kepala Madrasah dalam Mengembangkan Budaya Organisasi yang Inklusif dan Berdaya Saing di Lembaga Pendidikan Islam - Adawiyah, Robiatul; Ummah, Fiena Saadatul (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine the visionary leadership of madrasah heads in developing an inclusive and competitive organizational culture in Islamic educational institutions. This study uses a literature study method to identify and analyze the results of previous research that are relevant to the topic. The source of data for this research comes from various articles published through google scholar, Journal, and PubMed. The data analysis technique used is qualitative data analysis consisting of data reduction, data presentation, and conclusion drawing. The findings of this research are that the visionary leadership of the head of the madrasah is the ability of the head of the madrasah to create, formulate, communicate, and implement ideal ideas that come from him or the result of social interaction among madrasah members as the ideals of the madrasah in the future that must be achieved or realized through the commitment of all personnel. The development of organizational culture in schools cannot be separated from the leadership role of the principal as the main actor who determines and colors the lives of school residents. The visionary leadership of the head of the madrasah must be able to create a conducive organizational culture. The same steps and vision in carrying out duties and responsibilities must be possessed by each member so that everyone can improve his or her professionalism.